Effects of Derivatization on the Metabolite Profiling of the Cadmium-Tolerant Mangrove Fungus Trichoderma atroviride Using GC-MS Analysis - Siti Athirah Mohamad Jamali; Kamalrul Azlan Azizan; Syarul Nataqain Baharum; Mariam Taib (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2022)
The mangrove fungus Trichoderma atroviride was found to be tolerant to the heavy metal cadmium and it is of high interest to profile its metabolites to gain insight into its response to cadmium toxicity. This study aimed to investigate the effect of derivatization agents on the number and types of metabolites present in the cadmium-tolerant T. atroviride, detected using GC-MS analysis. The intracellular and extracellular metabolites of T. atroviride treated with cadmium for ten days were derivatized using silylation and alkylation reactions. The results showed that a higher number of metabolites were identified when the three different derivatization agents were used: BSTFA, TBDMSTFA, and MCF. More types of metabolites were identified by silylation, making it suitable for non-targeted metabolites profiling study. Silylation is efficient for the analysis of sugars and their derivatives while alkylation is suitable for a targeted study involving amino acids and organic acids. Statistical analysis for the data set of identified metabolites was performed using Metaboanalyst 3.0 followed by visualization using Partial Least Square-Discriminant Analysis. The plots showed clear separations of metabolites between the different types of derivatization agents and between control and cadmium-treated samples. A more comprehensive metabolite profile of T. atroviride obtained using different derivatization agents in this study, followed by distinct metabolites detected between control and treated samples, will provide good baseline information for future investigations including the pathways and biomarkers responsible for the fungal tolerance to cadmium toxicity.